PERAN KOMPETENSI KEWIRAUSAHAAN KEPALA SEKOLAH DALAM PENINGKATAN MUTU PENDIDIKAN DI SMAN 1 MAKARTI JAYA - Sariyasni Sariyasni; Budiyono Budiyono (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This research aims to reveal the role of the principal’s entrepreneurship competency in the SMAN 1 Makarti Jaya, in 2018/2019 viewed from: 1) context, 2) input, 3) process, and 4) product of the role of the principal’s entrepreneurship competency. The data were collected through interviews, and analyzed descriptively. The role of the principal’s entrepreneurship competency in improving the quality of the education can be seen through the CIPP models of the research. Teh context is to determine the relevance of the program to the needs of the school policy. The input is to identify the school readiness. The process is for determining the school activities. The product is to determine the quality of the school in terms of the number of graduates. The results are as follows 1. The context is good, because of the relevance of the program according to the needs of the school. 2. The input is good, in the form of school readiness including: infrastructure, teachers, students, and principals to implement the program with clear targets. 3. The program implementation process is good, because the participation of teachers and students, quality of teaching, extracurricular increased, and the prin-cipals are able to manage all school activities. 4. The product is good, in the form of: (a) academic achievement in the National Examination achievement, (b) non academic achievement, and (c) students’ winning various competitions.There fore the role of the principal’s entrepreneurship compe-tency is said to be good and successful.